Pengaruh Anggaran Partisipatif terhadap Kinerja Manajerial - Iin Indarti (STIE Widya Manggala, 2009)
This research is done in order to know the impact between the participative budgeting and managerial performance. The examination will be as follow ; is the motivation able to act its role as the intervening variable, in the relation between the participative budgeting and the managerial performance? The function of budget in the company is not only as a tool of planning, but also as a working guide, coordination tool, control tool and working evaluation tool. Because of the close relation between the function of budget and function of the management, the relationship between participative budget and the management performance has attracted the attention for obdseravtion. The regression analysis used the data analysis technique. Finally, the research results showed that the participative budgeting has a positive impact to the managerial performance, but not significant, and the participative budgeting has the positive impact to the managerial performance, but not significant. Motivation has the positive and significant impact to the managerial performance. In other word, motivation can not be used as the intervening varibel, because the observation results showed that the participative budgeting and motivation have the positive impact to the managerial performance but not significant.